PENINGKATAN KESADARAN DAN KETERAMPILAN LITERASI DIGITALDALAM MASYARAKAT MULTIKULTURAL SEBAGAI UPAYA MENUJU SDGS 2030 - Nova Lestari; Yolanda Elfantarosa Mengko; Ichsan Fauzi Rachman (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
Technological progress is one of the reasons for developing skills and awareness towards sustainable development in accordance with the SDGs goals. One effort that can be made is to develop digital literacy so that inequality and poverty are reduced or even non-existent. This is one of the goals of the SDGs, all of which have 17 goal points. These problems are problems faced in the world, even in Indonesia. To make this happen, especially for multicultural communities, digital literacy is needed. With its diversity potential, it will be a great opportunity to build multicultural relationships that understand digital literacy. This research aims to provide in-depth insight into the importance of awareness and digital literacy skills in multicultural societies to realize the 2030 SDGs. This research is a literature review using library study data collection techniques. From the results of the analysis, society's multicultural knowledge is always related to the understanding of the existence of cultures other than one's own. It is hoped that digital literacy can form an intelligent society that is sensitive to changes in technology and times. Educating the public about how to utilize the digital world is one way to advance the economy